The holistic support for a patient with end-stage chronic disease and primary caregivers under the doctor-nurse-social worker trinity model (医-护-社三位一体照护模式下1例慢性病终末期患者及其主要照顾者的整体支持) - LI Haoran (李浩然); MENG Xiangnan (孟祥楠) (中西医结合护理)
This article summarized the practice of holistic support for a patient with end-stage chronic disease and primary caregivers under the doctor-nurse-social worker trinity model. Given the illness condition of the patient, comfortable nursing interventions were carried primarily, followed by a comprehensive evaluation on family background and holistic support for the primary caregiver. Moreover, holistic support under the doctor-nurse-social worker trinity model aims to relieves the stress of primary caregivers, reduce the pain and improve the quality of life of the patient with end-stage chronic disease. (本文总结医-护-社三位一体照护模式下1例慢性疾病终末期患者及其主要照顾者整体支持的实践经验。针对终末期患者的特殊情况, 首先控制不适症状, 给予舒适护理; 其次充分了解患者家庭背景, 给予系统支持; 协调沟通家庭关系, 缓解主要照顾者精神压力, 从而减轻患者痛苦, 提高生命质量。)